Development for a quality improvement training programme for health professionals in the ministry of health and social services in Namibia - Nangombe, Julia Paul; Amukugo, Hans Justus (International Journal of Health, 2016)
The paper describes the steps followed in the development of a quality improvement training programme for health professionals. This was echoed by the facts that the health professionals are facing in their quest for quality health care delivery. In Namibia, most health care facilities have not been yielding good results in response to patients’ health care needs. Health care dynamics are complex and inundated with several factors; among others new methods, speed of improving medical science and technology, as well as increasing demands of the clients to address emerging and re-emerging diseases.In order to achieved that the five phases of programme development by Meyer and Van Niekerk (2008) were modified to facilitate the programme development. Quality improvement training for health professionals. Those five phases were situational analysis; conceptual framework; developing of the training programme; development of the guidelines for the implementation; and Evaluation of training programme.